The Medical Library Assistance Act: An Analysis of the NLM Extramural Programs, 1965-1970 - Cummings, Martin M. (1971)
The imbalance between medical library resources and information needs of the health professional led to a reexamination of the mandate for the National Library of Medicine. Legislation known as the Medical Library Assistance Act (MLAA) was passed in 1965 which enabled the NLM to (1) initiate programs to assist the nation's medical libraries and (2) develop a medical library network with the establishment of regional medical libraries to link the NLM with local institutions. The National Library of Medicine, through the MLAA, has made available $40.8 million to the medical library community under a competitive grant and contract mechanism for the period July 1965—June 1970. A total of 604 projects has been executed in resources, research and development, training, construction, regional medical libraries, publications, and special scientific projects. An assessment is given of each of these programs and their impact on both the National Library of Medicine and individual medical libraries. In the aggregate, these programs have significantly improved library and information services to the professional health user. The principal limitation has been inadequate funding to accomplish the level of originally stated objectives.